EFL Teachers’ Competence in the Context of English Curriculum 2004: Implications for EFL Teacher Education - Lengkanawati, Nenden Sri (TEFLIN Journal, 2015)
This is a report of a study which was intended to respond to criticism of the English curricula used in Indonesia which have been claimed by some as failure to make Indonesian students ready in competing with those from other nations. The study tried to portray EFL teachers’ competence in West Java and the implications for teacher education. Using a descriptive method, the study investigated proficiency of English teachers in West Java as a tool to assess their readiness in facing the challenge of the implementation of the 2004 English Curriculum and its implication for teacher education. The data concerning teachers’ proficiency in Listening, Structure, and Reading Comprehension were collected using a TOEFL-eq